Comparison of the Effects of Eicosapentaenoic Acid and Docosahexaenoic Acid on the Eradication of Helicobacter pylori Infection, Serum Inflammatory Factors and Total Antioxidant Capacity - Khandouzi, Nafiseh (Iran J Pharm Res, 2015)
Helicobacter pylori infection, the most common chronic bacterial infection in the world, and an important cause of gastrointestinal disorders, may be involved in the pathogenesis of some extra-gastrointestinal disturbances, as well as an increase in blood levels of certain inflammatory markers. Anti-bacterial activity against Helicobacter pylori and anti-inflammatory properties of omega-3 fatty acids have been studied in several research studies. The purpose of the present study was the comparison of the effects of Eicosapentaenoic Acid and Docosahexaenoic Acid supplementation on Helicobacter pylori eradication, serum levels of some inflammatory markers and total antioxidant capacity. In a randomized, double-blind, placebo-controlled clinical trial, 97 Helicobacter pylori positive patients (64 patients in the two intervention groups and 33 in the control group), received 2 grams daily of Eicosapentaenoic Acid, Docosahexaenoic Acid or Medium Chain Triglyceride oil as placebo, along with conventional tetra-drug Helicobacter pylori eradication regimen, for 12 weeks. Helicobacter pylori eradication test and measurement of concentration of interleukine-6, interleukine-8, high-sensitivity C-reactive protein and total antioxidant capacity were performed after the intervention. There was no significant difference in eradication rate of the infection, levels of interleukine-6 and total antioxidant capacity among the three groups, while the levels of interleukine-8 and high-sensitivity C-reactive protein were statistically different. Eicosapentaenoic Acid or Docosahexaenoic Acid supplementation had no significant differential impact on the eradication of Helicobacter pylori infection, and serum levels of interleukine-6 and total antioxidant capacity. However, it had a desirable effect on the levels of interleukine-8 and high-sensitivity C-reactive protein in Helicobacter pylori positive patients.